Determination of the Boltzmann constant k from the speed of sound in helium gas at the triple point of water. (19th August 2015) - Pitre, L; Risegari, L; Sparasci, F; Plimmer, M D; Himbert, M E; Giuliano Albo, P A
Abstract: The Boltzmann constant k has been determined from a measurement of the speed of sound in helium gas in a quasi-spherical resonator (volume 0.5 l) maintained at a temperature close to the triple point of water (273.16 K). The acoustic velocity c is deduced from measured acoustic resonance frequencies and the dimensions of the quasi-sphere, the latter being obtained via simultaneous microwave resonance. Values of c are extrapolated to the zero pressure limit of ideal gas behaviour. We find J⋅K −1, a result consistent with previous measurements in our group and elsewhere. The value for k, which has a relative standard uncertainty of 1.02 ppm, lies 0.02 ppm below that of the CODATA 2010 adjustment.